RETRACTED ARTICLE: MicroRNA-210 protects against periodontitis through targeting HIF-3α and inhibiting p38MAPK/NF-κB pathway - Shuyu Jia; Ximei Yang; Xirong Yang; Fei Zhang (Artificial Cells, Nanomedicine, and Biotechnology)
We, the Editors and Publisher of the journal Artificial Cells, Nanomedicine, and Biotechnology, have retracted the following article:Shuyu Jia, Ximei Yang, Xirong Yang & Fei Zhang. (2020). MicroRNA-210 protects against periodontitis through targeting HIF-3α and inhibiting p38MAPK/NF-κB pathway. Artificial Cells, Nanomedicine, and Biotechnology, 48(1), 129–136, DOI: 10.1080/21691401.2019.1699818Since publication, concerns have been raised about the integrity of the data in the article. When approached for an explanation, the authors have been unable to provide their original data. The authors have agreed to the retraction of the article.We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions.The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as ‘Retracted’.